Beyond economic data: softer, subjective indicators of a nation’s well-being - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2009)
A society, fuelled by trust and cooperation, should rank highly on life satisfaction and happiness. Traditional measures of well-being, however, largely overlook these factors, and rely mostly on economic data. In the paper, “The well-being of nations: linking together trust, cooperation and democracy”, William Tov, a social science professor at Singapore Management University (SMU), discusses the social implications of well-being for individuals and society at large.